EFEKTIVITAS PELATIHAN PENELITIAN TINDAKAN KELAS MELALUI MODEL PEMBELAJARAN ADIK PKL ABG DAN APLIKASI GOOGLE CLASSROOM DI KOTA SUKABUMI - Firdos Mujahidin (Balai Diklat Keagamaan Banjarmasin, 2021)
Training during pandemic requires learning models and applications to support its effectiveness, including in Class Action Research (PTK) training. The aims of this study is to find out the effectiveness of PTK training through ADIK PKL learning model and Google Classroom (GCR) application in Sukabumi City. The research method uses action research approach with qualitative descriptive method. Data collection techniques were compiled through observation activities, knowledge tests and performance tests of trainees and qualitatively analyzed. The research was conducted for PTK training participants of Madrasah Aliyah (MA) Teachers, Sukabumi City 2021. The results showed that ADIK PKL ABG learning model supported by GCR application can manage learning effectively. It can be seen from the average attitude score which is 94.73 and average test score for knowledge is 79.93. The participants also skillfully composed a predetermined learning product with an average skill score 89.27 and average final score 87.98. ADIK PKL ABG learning model and Google Classroom application can also be separated in the training, but the learning will be more effective if those two are combined.